Arahan Pengembangan Wisata Pantai Indah Bosowa di Kota Makassar - Lelepadang, Nadya Tiara Rendeng; Aksa, Kamran; Taking, Muhammad Idris (Fakultas Teknik Universitas Bosowa, 2023)
The purpose of this study was to find out the factors that influence the lack of maximum tourism development at Indah Bosowa beach, Makassar city, knowing the direction of tourism development at Indah Bosowa Beach. This type of research is a multi methods research. To analyze what factors influence the lack of maximum tourism development on Indah Bosowa beach using chi-square analysis to find out the direction of development used Bayes analysis. The main conclusion in this study is based on the results of chi-square analysis indicating that the factors influencing tourism development at Pantai Indah Bosowa are aspects of attractiveness, promotion and marketing, and facilities and services. The direction of development carried out is to increase the number of facilities and services, use promotional methods through advertising and endorsement techniques and create a master plan concept for the Pantai Indah Bosowa planning area.